Dialogue editing for motion pictures : a guide to the invisible art - Purcell, John, 1957- (London : Focal press, 2007)
"In Dialogue Editing for Motion Pictures, Second Edition veteran film sound editor John Purcell arms you with classic as well as cutting-edge practices to effectively edit dialogue for film, TV, and video. This new edition offers: - A fresh look at production workflows, from celluloid to Digital Cinema, to help you streamline your editing - Expanded sections on new software tools, workstations, and dialogue mixing, including mixing "in the box" - Fresh approaches to working with digital video and to moving projects from one workstation to another - An insider's analysis of what happens on the set, and how that affects the dialogue editor - Discussions about the interweaving histories of film sound technology and film storytelling - Eye-opening tips, tricks, and insights from film professionals around the globe - A companion website (www.focalpress.com/cw/purcell) with project files and video examples demonstrating editing techniques discussed in the book Don't allow your dialogue to become messy, distracting, and uncinematic! Do dialogue right with John Purcell's all-inclusive guide to this essential yet invisible art"--
Includes bibliographical references and index.
Keywords: Motion pictures -- Sound effects; Sound motion pictures; PERFORMING ARTS / Film & Video / General